Dynamic interplay of transcription factors during the response to oxidative stress - Goldstrohm, David Allen, author; Stargell, Laurie, advisor; Laybourn, Paul, committee member; Luger, Karolin, committee member; Mykles, Donald, committee member; Paule, Marvin, committee member (Colorado State University. Libraries, 2006)
Complex biological phenomena such as cell growth, response to environmental change, development of multicellular organisms, and disease, are all directly influenced by transcriptional regulatory mechanisms. These mechanisms are fundamentally similar in all eukaryotic organisms. Therefore, understanding transcriptional regulatory mechanisms in less complex eukaryotic organisms such as yeast, will lead to a greater knowledge of similar processes in human cells. Oxidative stress is linked to numerous deteriorating conditions including cancer, neurodegenerative diseases, atherosclerosis, alcohol-induced liver damage, and aging. In yeast, as in humans, the oxidative stress response is regulated at the level of transcription, thus making yeast a useful model system of study. Here we propose a model for transcriptional activation of RNA polymerase II (Pol II) gene expression during the response to oxidative stress. This work reveals the oxidative stress inducible gene FLR1 functions through a noncanonical core that contains a relatively complete inert preinitiation complex (PIC) prior to gene activation. Further studies show that phosphorylation of the carboxy-terminal domain (CTD) of Pol II is not sufficient for PIC activation, which is ultimately achieved by activator-dependent recruitment of Mediator to the FLR1 promoter. In addition, the essential subunits of Mediator required for cell growth during nonoptimal conditions are characterized and grouped into novel Mediator modules. Overall, these findings reveal a two-step mechanism for transcriptional activation involving the combinatorial function of sequentially acting activators. This model suggests the activation of gene expression during oxidative stress is more complex than classical models demonstrate and supports a cooperative role for the function of activator proteins. Collectively, this entire body of work contributes significantly to a greater understanding of the transcriptional regulatory mechanisms for cell survival during oxidative stress conditions. Ultimately, with this knowledge treatments may be developed to combat the harmful diseases that result from the misregulation of similar stress response processes in human cells.
Keywords: biochemistry